Associations between dairy consumption, physical activity, and blood pressure in Chinese young women - Lu, Yining; Wiltshire, Huw D.; Baker, Julien S.; Wang, Qiaojun; Ying, Shanshan (Frontiers in Nutrition, 2023)
Introduction The prevalence of hypertension (HTN) has been increasing in young adults. A healthy dietary pattern and increasing physical activity (PA) are commonly recommended as lifestyle modifications needed to manage blood pressure (BP). However, little is known about the relationship between dairy intake, PA, and BP in Chinese young women. The aim of this study was to examine whether BP was associated with dairy intake, moderate-to-vigorous intensity physical activity (MVPA) and total physical activity (TPA) in a sample of Chinese young women. Methods A total of 122 women (20.4 ± 1.4) who had complete data sets from the Physical Fitness in Campus (PFIC) study were included in this cross-sectional analysis. Data related to dairy intake and PA was collected using a food frequency questionnaire and an accelerometer. BP was measured following standardized procedures. The association between BP with dairy intake and PA was examined using multivariable linear regression models. Results After controlling for potential covariables, we observed a significant and independent relationship only between systolic BP with dairy intake [standardized beta (b) = −0.275, p < 0.001], MVPA (b = −0.167, p = 0.027), and TPA (b = −0.233, p = 0.002). Furthermore, we found a decrease of 5.82 ± 2.94, 1.13 ± 1.01, and 1.10 ± 0.60 mm Hg in systolic BP for daily additional servings of dairy, 10 min of MVPA, and 100 counts per minute of TPA, respectively. Conclusion Our results suggested that the higher amount of dairy consumption or PA was associated with lower level of SBP in Chinese young women.